English: English - Syarifah, Syarifah (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
This research looks into how the magical and real worlds exist side by side in Lady Midnight by Cassandra Clare, using a postmodern perspective. It shows how both worlds interact and function within the same space and time. Drawing on Marcel Mauss’s theory of magic and postmodern ideas, the study reveals that magic in the novel isn’t shown as the opposite of reality, but rather as a parallel system that reflects similar structures and social patterns. The analysis suggests that postmodern stories often blur the lines between reality and fantasy, questioning fixed boundaries and supporting more flexible ways of understanding the world.